PENGEMBANGAN E-BOOK BERBASIS KETERAMPILAN 4C ABAD 21 PADA MATA KULIAH KONSEP DASAR IPS: PENGEMBANGAN E-BOOK BERBASIS KETERAMPILAN 4C ABAD 21 PADA MATA KULIAH KONSEP DASAR IPS - Nasution, Yusra; Husna Parluhutan Tambunan; Masta Marselina Sembiring; Dody Feliks Pandimun Ambarita; Dila Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research aims to develop an e-book product for Basic Social Sciences Concepts in the feasible and effective category. Research approach with Research and Development (R&D) ADDIE model. The sample consisted of 30 people from class B PGSD 2023. The instrument used questionnaires and tests. The feasibility results obtained from material expert validators (3.80 and 4.80) and design experts (3.83), prove that the e-book meets the eligibility criteria. The e-book effectiveness test was obtained at 93.3% and the difference in value was 43.133. Effectiveness of e-books effective criteria. The research findings show that the 21st century 4C ability-based social studies e-book is feasible and efficient for students to use.